2024
DOI: 10.1001/jamanetworkopen.2023.53771
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Access to Buprenorphine for Opioid Use Disorder

Andrew A. Herring,
Allison D. Rosen,
Elizabeth A. Samuels
et al.

Abstract: ImportanceAlthough substantial evidence supports buprenorphine for treatment of opioid use disorder (OUD) in controlled trials, prospective study of patient outcomes in clinical implementation of emergency department (ED) buprenorphine treatment is lacking.ObjectiveTo examine the association between buprenorphine treatment in the ED and follow-up engagement in OUD treatment 1 month later.Design, Setting, and ParticipantsThis multisite cohort study was conducted in 7 California EDs participating in a statewide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“… 34 Potentially, early and sustained administration of relatively high levels of buprenorphine that avoid any significant between-dose trough would assist with retention. This percentage of engagement in treatment at 7 days was higher than ED implementation studies of sublingual buprenorphine that have reported 35.8% 35 and 48% 36 , 37 rates of engagement at 30 days post-ED–initiated buprenorphine. A shorter time assessment and the presence of well-established referral community partners may have contributed to this difference.…”
Section: Discussionmentioning
confidence: 54%
“… 34 Potentially, early and sustained administration of relatively high levels of buprenorphine that avoid any significant between-dose trough would assist with retention. This percentage of engagement in treatment at 7 days was higher than ED implementation studies of sublingual buprenorphine that have reported 35.8% 35 and 48% 36 , 37 rates of engagement at 30 days post-ED–initiated buprenorphine. A shorter time assessment and the presence of well-established referral community partners may have contributed to this difference.…”
Section: Discussionmentioning
confidence: 54%